2019 Italian Society of Cardiology Census on telemedicine in cardiovascular disease: a report from the working group on telecardiology and informatics. Issue 1 (17th March 2020) - Brunetti, Natale Daniele; Molinari, Giuseppe; Acquistapace, Flavio; Zimotti, Tecla; Parati, Gianfranco; Indolfi, Ciro; Fedele, Francesco; Carugo, Stefano
Abstract : Background: The aim of this study was to assess by a census supported by the Italian Society of Cardiology (Società Italiana di Cardiologia, SIC) the present implementation of telemedicine in the field of cardiovascular disease in Italy. Methods: A dedicated questionnaire was sent by email to all the members of the SIC: data on telemedicine providers, service provided, reimbursement, funding and organisational solutions were collected and analysed. Results: Reported telemedicine activities were mostly stable and public hospital based, focused on acute cardiovascular disease and prehospital triage of suspected acute myocardial infarction (prehospital ECG, always interpreted by a cardiologist and not automatically reported by computerised algorithms). Private companies delivering telemedicine services in cardiology (ECGs, ambulatory ECG monitoring) were also present. In 16% of cases, ECGs were also delivered through pharmacies or general practitioners. ICD/CRT-D remote control was performed in 42% of cases, heart failure patient remote monitoring in 37% (21% vital parameters monitoring, 32% nurse telephone monitoring). Telemedicine service was public in 74% of cases, paid by the patient in 26%. About half of telemedicine service received no funding, 17% received State and/or European Union funding. Conclusions: Several telemedicine activities have been reported for the management of acute and chronic cardiovascular disease in Italy. The whole continuum of cardiovascular disease is covered by telemedicine solutions. A periodic census may be useful to assess the implementation of guidelines recommendations on telemedicine.